Dynamic tensile and compressive behaviour of AA7475-T7351 alloy under different strain rates and temperatures. (December 2022) - Chakraborty, Purnashis; Singha, M.K.; Tiwari, Vikrant
Abstract: The mechanical behaviour of the aluminium alloy AA7475-T7351 under different loading rates and temperatures is investigated in this article. The high strength AA7475-T7351 alloy under consideration, with its quasi-static tensile strength of 560 MPa at room temperature (25 °C), is stronger than most other aluminium alloys. At the beginning, the specimens are evaluated under quasi-static tension and compression along the rolling direction at five different temperatures (25 °C, 100 °C, 150 °C, 200 °C and 250 °C) on a universal testing machine. Thereafter, an extensive experimental study is conducted on the Split Hopkinson pressure bar set up (SHPB) and the tensile Hopkinson bar (SHTB) to study the constitutive behaviour of AA7475-T7351 specimens at higher strain rates (up to +3000 s −1 for tensile and −4400 s −1 for compression) and elevated temperatures. The strength and ductility of AA7475-T7351 are observed to depend on the loading direction (tension/compression), strain rate and temperature. The efficiencies of the two widely used constitutive models (Johnson-Cook and KHL) for predicting the mechanical behaviour of AA7475-T7351 are also examined.